Keselarasan Iman Dan Perbuatan Dalam Teologi Keselamatan Menurut Erastus Sabdono - Tang Aldi Yabes; Yusuf Setiawan Sudarso Kusumo (Sekolah Tinggi Teologi Ekumene Jakarta., 2024)
Salvation is a free gift from God. Such salvation has an impact on four things as emphasized by Erastus Sabdono, namely redemption, the Holy Spirit, the Gospel, and God's cultivation. The fundamental issue that is often discussed around salvation is the relationship between faith and actions. Which is more important? Or are both done simultaneously? This article discusses an overview of the theological basis for the harmony of faith and works in salvation theologies. Due to the wide area of ​​discussion, the researcher focused on the ideas of Erastus Sabdono. The research method used by researchers to explore this is literature study of books and journals as well as direct interviews with Erastus Sabdono. The research results show that Erastus Sabdono's theology of salvation is in line with what James 2:14-26 conveys.